PRODUÇÃO DE ÁCIDO PROPIÔNICO A PARTIR DE EFLUENTES AGROINDUSTRIAIS - Moreira, Debora Christina (2013)
The search for renewable energy and food production with the minimum threat to the environment are themes that have been studied for all over the world. Several processes have been developed for the use of agroindustrial wastes, transforming them into chemical compounds and products with high added value. The use of agroindustrial wastes in bioprocesses helps the search for sustainable processes. The increasing in the agricultural productivity in Brazil, open a new market to the development of researches that study this issue. The statistical modeling of mixtures, allied with the design of experiments, has application in a several industrial systems. The aim of this work was to study the possibility of use agroindustrial wastewater mixtures to produce propionic acid. Four types of wastewater were studied: corn steep liquor, pet food wastewater, meat processing wastewater and dairy wastewater. Assays were performed to obtain the best composition of the mixtures and the best substrate ratio. Within the conditions employed, the mixture containing 75% of corn steep liquor and 25% of another substrate, were most suitable for the process. Studying the tests in which the fermentations conditions varied (boiling the substrate, agitation and pH correction to 6,5) the best concentrations of propionic acid, 229,57 mg.L-1, were produced by mixing 75% of corn steep liquor and 25% of pet food wastewater, after 72h of fermentation, with initial correcting of pH to 6,5, followed by the mixture containing 75% of corn steep liquor and 25% of meat processing wastewater, that enabled the production of 154,27 mg.L-1 of propionic acid. The mixture with 75% of corn steep liquor and 25% of dairy wastewater with daily pH correction enabled the production of 220,96 mg.L-1 of propionic acid after 72 hours of fermentation. The other essay conditions were not significant for propionic acid biosynthesis. The statistical analysis confirms that it is possible to use codigestion agroindustrial waste for propionic acid production.